Umat Islam di Filipina Selatan: Sejarah, Perjuangan, dan Rekonsiliasi - Saifullah SA Saifullah SA (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2008)
This paper deals mainly with the political struggle of the people of Southern Philippine for independence. To a large extent, this paper is about the investigation of the political ideology of these people. To start with, the paper distinguishes between two opposing groups, namely the government and the Muslim group demanding for independence. The Muslims in their turn were then classified into two groups, the one is radical pursuing for political change through political ?often violent- activities, and the other is moderate urging for a better life especially for Muslims through a peaceful, constructive, legal, and constitutional means. The paper argues that the government of the Philippine has shown its willingness to find ways of solving the problems through dialogue and peace process. The paper is also interested in discussing the view expressed by Peter Gowing who believes that in the near future the Muslims of the Philippine would be divided into two groups. The one successfully forms autonomous quasi-independent Muslim territories, and the other sticks to the national government having a strong consciousness to work toward the national integration and harmony.